Analisis Kesiapan Guru Dalam Implementasi Kurikulum 2013 Berdasarkan Rpp Tahun 2014 Sd Muhammadiyah 21 Baluwarti - Ashri, Ammar Nur; , Minsih, S.Ag, M.Pd (2017)
This study aims to describe the readiness of teachers in the implementation of Curriculum 2013 based on the RPP 2014, explaining the constraints faced by teachers and to describe the follow-up in the implementation of Curriculum 2013 SD Muhammadiyah 21 Baluwarti. This type of descriptive qualitative research and case study research design. Data collection techniques used interviews and documents. The validity of this research data using source and technique triangulation. Data analysis techniques in this study data collection techniques and analysis strategies. The results of the discussion of the readiness of teachers in SD Muhammadiyah 21 Baluwarti related to the implementation of Curriculum 2013 based on RPP, teachers who are ready in the implementation of Curriculum 2013 is teacher class II and teachers who aren't ready is teacher class IV and class V in terms of administrative completeness ranging from planning and preparation RPP, implementation of learning, and assessment. Constraints faced by teachers in the implementation of Curriculum 2013 include: (1) Planning, one teacher complained in the preparation of RPP is to modify the material, and determine the teaching materials; (2) Implementation, two teachers difficult to enter the material during the learning because students are still busy to play so that the material can't be accepted by students well; (3) Assessment, the three teachers complained about the judgment in terms of administration which was too time consuming, laborious, and the cost due to the teacher age factor of most senior teachers. Follow-up by teachers to overcome obstacles encountered that involve other parties such as collaborating, discussing, consulting and providing input with colleagues. Support, monitoring and direction from the principal is also a follow-up in the implementation of Curriculum 2013, as well as follow the training related Curriculum 2013.